PEMETAAN FAKTOR RISIKO KEJADIAN HIPERTENSI PADA USILA DIWILAYAH PUSKESMAS PAMBOANG KABUPATEN MAJENE PROVINSI SULAWESI BARAT - Budianto Wiryodinomo; Muhrawi Yunding; Ainun Rafiqah Masykur; Aswardi Arrida; Imran Yaman (LPPM STIKES Marendeng Majene, 2022)
Abstract. Hypertension is also known as high blood pressure, with a systolic pressure that stays above 140 mmHg and a diastolic pressure that stays above 90 mmHg. This research was conducted with the aim to determine the risk factors of hypertension in the elderly in region Puskesmas Pamboang Majene, West Sulawesi. This study uses adesign. case control study.The number of samples in this study as many as 70 cases and 70 controls so that the total sample of 140 respondents. The results of this study indicate that gender is a risk factor of hypertension in elderly with OR = 1.465; 0.726 to 2.957, a family history of hypertension at risk factors of hypertension in the elderly with OR = 2.745; 1.376 to 5.476 and most numerous in the Bonde, smoking is a risk factor for hypertension in the elderly with OR = 3.576; 1.604 to 7.973 and at most in the Lalampanua, caffeine consumption habits are risk factors for hypertension in the elderly with OR = 2.647; 1.316 to 5.325 and is widely available in the Tinambung, salted fish consumption habits are risk factors for hypertension in the elderly with OR = 2.138; 1.085 to 4.212 and is widely available in the Tinambung. Conclusion : of all the risk factors for hypertension, smoking is the most at risk for the incidence of hypertension with an OR = 3,576 It is hoped that routine blood pressure checks are carried out at least once a month for early detection of hypertension